Nonhuman primates at the intersection of aging biology, chronic disease, and health: An introduction to the American Journal of Primatology Special Issue on aging, cognitive decline, and neuropathology in nonhuman primates. Issue 11 (17th August 2021) - Shively, Carol A.; Lacreuse, Agnès; Frye, Brett M.; Rothwell, Emily S.; Moro, Manuel
Abstract: Aging across the Primate Order is poorly understood because ages of individuals are often unknown, there is a dearth of aged animals available for study, and because aging is best characterized by longitudinal studies which are difficult to carry out in long‐lived species. The human population is aging rapidly, and advanced age is a primary risk factor for several chronic diseases and conditions that impact healthspan. As lifespan has increased, diseases and disorders of the central nervous system (CNS) have become more prevalent, and Alzheimer's disease and related dementias have become epidemic. Nonhuman primate (NHP) models are key to understanding the aging primate CNS. This Special Issue presents a review of current knowledge about NHP CNS aging across the Primate Order. Similarities and differences to human aging, and their implications for the validity of NHP models of aging are considered. Topics include aging‐related brain structure and function, neuropathologies, cognitive performance, social behavior and social network characteristics, and physical, sensory, and motor function. Challenges to primate CNS aging research are discussed. Together, this collection of articles demonstrates the value of studying aging in a breadth of NHP models to advance our understanding of human and nonhuman primate aging and healthspan. Abstract : Mouse lemur (Photo Credit: Eric Gueton), Common marmosets (Photo Credit: Agnès Lacreuse); Barbary macaque (Photo Credit: Julia Fischer); Chimpanzee "Cobby" (Photo Credit: Marianne Hale); Long‐tailed macaque (Photo Credit: Entang Iskandar); Rhesus macaque (Photo Credit: Kathy West); Vervet monkey (Photo Credit: Brett M. Frye). Compilation Design by Carol A. Shively. Research Highlights: Aging across the Primate Order is poorly understood due to a lack of aged animals, longitudinal studies, and funding. The human population is aging rapidly, and advanced age is a primary risk factor for several chronic diseases and conditions that impact healthspan. Studying aging in a breadth of NHPs will advance our understanding of human and nonhuman primate aging and promote interventions that increase healthspan.